Geodynamic evolution of southwestern North America since the Late Eocene - Alireza Bahadori (Nature Portfolio, 2019)
The tectonic evolution of southwestern North America remains debated. Here, the authors present a complete time-dependent geodynamic model of the tectonic evolution of southwestern North America, which can explain the extensional collapse of the Basin and Range Province since the Late Eocene.